The impact of local and foreign film censorship on young adult’s behaviour in Malaysia: A narrative literature review - Amran, Nur Ainul Basyirah (EDUCATUM Journal of Social Sciences, 2025)
The Malaysian government's Film Censorship Board, known as Lembaga Penapis Filem, has been in charge of film censorship for the past few years (LPF). Therefore, this research aims to examine the impact of local and foreign film censorship on young adult’s behaviour in Malaysia. This study is based on qualitative data obtained through a narrative literature review, drawing from fifteen journal articles about the research topic identified using Google Scholar from 2019 to 2023. According to the survey, there is a worrying trend among Malaysian young adults. They are becoming more likely to access sensitive information against the LPF's restrictions, especially in areas like politics, religion, and homosexuality. This conduct not only highlights a violation of censorship standards but also acts as an influence in influencing the opinions, convictions, and cultural awareness of the young adult population. According to the study, these encounters have a big impact on how people understand and adhere to social norms. In essence, this study contributes to a better understanding of how cinema censorship affects the psychological aspects of media consumption among Malaysian young adults. Essentially, this study adds to the growing body of knowledge regarding how Malaysian young adults' psychological media use is affected by cinema censorship. In summary, the study helps policymakers develop a paradigm that takes into account the psychological aspects of media consumption in addition to offering a comprehensive understanding of the effects of local and foreign film censorship on young adult’s behaviour in Malaysia.